Maxwell’s Equations and Four Dimensions - Chattopadhyay, Rabindranath (Journal of Educational Research and Policies, 2024)
Maxwell equations is viewed under the 4th dimension Ct. Not with t as an evolution of events seen by Mikowski, but with τ of Planck’s inside in 1900. In other words, Cτ as proposed by the Autor in his theory of space in 2021, i.e. the 4th longitudinal dimension lambda; energy´s wavelength Cτ.